Bilateral transcutaneous tibial nerve stimulation for chronic constipation. (2nd February 2016) - Iqbal, F.; Collins, B.; Thomas, G. P.; Askari, A.; Tan, E.; Nicholls, R. J.; Vaizey, C. J.
Abstract: Aim: Chronic constipation is difficult to treat when symptoms are intractable. Colonic propulsion may be altered by distal neuromodulation but this is conventionally delivered percutaneously. Transcutaneous tibial nerve stimulation is noninvasive and cheap: this study aimed to assess its efficacy in chronic constipation. Method: Eighteen patients (median age 46 years, 12 female) with chronic constipation were recruited consecutively. Conservative and behavioural therapy had failed to improve symptoms in all 18. Thirty minutes of daily bilateral transcutaneous tibial nerve stimulation was administered by each patient at home for 6 weeks. The primary outcome measure was a change in the Patient Assessment of Constipation Quality of Life (PAC‐QoL) score. Change in Patient Assessment of Constipation Symptoms (PAC‐SYM), weekly bowel frequency and visual analogue scale (VAS) score were also measured. Results: Fifteen patients (12 female) completed the trial. The PAC‐QoL score improved significantly with treatment [pretreatment, median 2.95, interquartile range (IQR) 1.18; posttreatment, median 2.50, IQR 0.70; P = 0.047]. There was no change in PAC‐SYM score (pretreatment, median 2.36, IQR 1.59; posttreatment, median 2.08, IQR 0.92; P = 0.53). Weekly stool frequency improved as did VAS score, but these did not reach statistical significance ( P = 0.229 and 0.161). The PAC‐QoL and PAC‐SYM scores both improved in four (26%) patients. Two patients reported complete cure. There were no adverse events reported. Conclusion: Bilateral transcutaneous tibial nerve stimulation appears to be effective in a quarter of patients with chronic constipation. Carefully selected patients with less severe disease may benefit more. This requires further study.